Spatial evaluation of the nutrient composition in mariculture zone, San Pedro Bay, Basey Samar - Alvarez, Jimboy C.; dela Cruz, Margarita T. (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Visayas Tacloban College, 2009)
Rapid assessment of the physico-chemical parameters and nutrient composition of the Basey, Mariculture Zone were investigated in the study to determine the general water quality. Five sampling stations were established and the parameters, which include water depth, water clarity or turbidity, surface water current, temperature, salinity, dissolved oxygen, percent saturation, total dissolved solids, pH and nutrient compositions of nitrates and phosphates were measured. Results showed that the concentration of nitrates and phosphates ranges from 0.418-6.917 mg/L and 0.147-0.430 mg/L respectively. These concentrations were still in the normal levels for marine environment. Nutrient levels are comparable to those obtained in the previous assessment of the Basey Mariculture Zone. Other parameters show little to no differences in the baseline data of the study site prior to its establishment.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.